'Wish to die' is independently associated with cardiovascular mortality in later life. Data from TILDA. (7th May 2021) - Ragab, Inas; Ward, Mark; Moloney, David; Kenny, Rose Anne; Briggs, Robert
Abstract: Background: There is an established bidirectional relationship between mental and heart health in later life but the link between wish to die (WTD) and cardiovascular mortality is less well‐defined. Methods: This is a longitudinal study examining the association between WTD and mortality over 9‐year follow‐up in a large population‐representative sample of older adults. Individual‐level survey data was linked to official death registration data, divided into cardiovascular and noncardiovascular causes. WTD was defined as answering affirmatively when asked 'In the last month, have you felt that you would rather be dead?' Regression models were used to obtain hazard ratios for the association between WTD at Wave 1 and mortality. Kaplan–Meier plots were used to compare survival across groups. Results: Just over 3% (275/8124) of participants reported WTD. Mortality data was available for 9% of participants (755/8124). WTD was significantly associated with all‐cause mortality, with a hazard ratio of 1.41 (95% confidence interval [CI]: 1.00–1.99). Findings were attenuated and no longer significant after excluding participants with heart disease or depression/anxiety/other psychiatric illness. WTD was significantly associated with cardiovascular mortality (hazard ratio: 2.14 [95% CI: 1.21–3.78]), even after excluding participants with depression/anxiety/other illnesses but not heart disease. WTD was not associated with an increased risk of death due to non‐cardiovascular causes. Conclusions: Older people who report a wish to die have double the risk of death from cardiovascular disease in the following 9 years, even when those with depression, anxiety or other mental health problems are excluded. Key points: Just over 3% of people aged ≥50 years reported a wish to die (WTD), endorsing that during the last month they have had thoughts that they would rather be dead. WTD was significantly associated with cardiovascular mortality during 9‐year follow‐up with a hazard ratio 2.14 (95% CI 1.21–3.78) in fully adjusted models. This association remained robust even after excluding participants with depression/anxiety/other psychiatric co‐morbidities but was no longer significant when participants with heart disease at baseline were excluded. WTD was not associated with an increased risk of death due to non‐cardiovascular causes.